PENGARUH KEBIASAAN BEROLAHRAGA, POLA HIDUP BERSIH DAN SEHAT TERHADAP KEJADIAN COVID-19 DI LINGKUNGAN MASYRAKAT DAN ANGGOTA IKATAN FISIOTERAPI INDONESIA KOTA BEKASI - Abdurahman Berbudi B L; Achwan Achwan; Ricca Andala Sari (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2021)
Background: Covid 19 virus (Corona virus disease) until now is a pandemic that has not been able to overcome the many victims caused by this virus, the West Java area is one of the largest red zone areas in Indonesia, the Indonesian Government has given an appeal to keep health by exercising and a clean and healthy lifestyle. The aim of this research is to determine the effect of sports habits on the application of clean and healthy living behavior in the community and members of the Indonesian physiotherapy association. The type of research used in this study is a descriptive survey, with 110 respondents. The data of this study were collected through filling out online questionnaires, from the results of the analysis of the data obtained it is known that exercise habits can prevent the transmission of covid 19 indicated by a value of p <0.05, and the effect a clean and healthy lifestyle against the occurrence of covid 19 transmission obtained a value of p <0.05, so it can be concluded that by doing sports and maintaining a clean and healthy lifestyle can prevent an increase in the incidence of covid 19 transmission.